Medição não invasiva do consumo de combustível em motores de combustão interna baseados no ciclo Otto - Emerson Alves da Silva (2020)
This work encompasses the development of a methodology for monitoring and measuring fuel consumption in internal combustion engines based on the Otto cycle equipped with a Common Rail injection system, and aimed to be non-invasive, to be assembled with low-cost electronics, and to present competitive accuracy levels compared to other existing measurement techniques. In this way, the measurement process is performed without cuts in the electrical conductors, insertion of components in the vehicle's original circuits, or even direct contact with the fuel fluid, preserving the vehicle's original characteristics. The technique proposes the measurement of electrical signals sent from the vehicle's electronic central to the fuel electro-injectors. Thus, the injection times are all recorded and converted into fuel mass using a calibration coefficient provided for in the modeling equation and found through a criterion proposed in this research. The effectiveness of the proposed methodology was tested on a Single Cylinder Research Engine (SCRE), equipped with all the necessary instrumentation to evaluate the effectiveness of the system. Thirty-two tests were performed, considering four different loads on the engine shaft, four different rotation speeds, and two different types of fuel, pure Ethanol (E100) and the mixture of Gasolina and 27% Ethanol (E27). The results were evaluated in terms of percentage errors, resulting from the deviation between the values observed in the measurements of the final consumed masses recorded by the gravimetric scale (reference) and the final mass measured by the prototype. The percentage errors obtained were lower than those indicated in the literature in electromechanical type sensors, and the total consumption measurement performed in Ethanol (E100) presented a maximum percentage error equal to ±2.9%, and for the Gasolina mixture and 27% Ethanol (E27) was equal to ±3.0%. Thus, it was concluded that the proposed objectives were achieved satisfactorily and with results consistent with other techniques proposed in the literature. It was also noticed that the methodology, based only on the measurements of electrical injection pulses, can be considered applicable to an unlimited range of flow and pressure.